UPAYA PENDEKATAN SOSIOLOGIS DALAM STUDI ISLAM - Maulana Ira (LPPM STISIP Persada Bunda, 2023)
Various problems faced by mankind today require the presence of religion as a solution. Religion is not only used as a symbol of piety alone, but conceptually is able to show an effective way of solving problems. Such demands can be answered when the understanding of religion that has been using a normative theological approach is also supported by other approaches that can operationally provide answers to problems that arise, one of which is a sociological approach. The urgency of the sociological approach in understanding religion is understandable because there are many religious teachings related to social problems. It is hoped that with a sociological approach, religion will be understood easily, because religion was revealed for social purposes